Kant and the mind - Brook, Andrew (Cambridge Cambridge University Press, 1994)
Kant made a number of highly original discoveries about the mind--about its ability to synthesize a single, coherent representation of self and world, about the unity it must have to do so, and about the mind's awareness of itself and the semantic apparatus it uses to achieve this awareness. The past fifty years have seen intense activity in research on human cognition. Even so, not only have Kant's discoveries not been superseded, some of them have not even been assimilated into current thinking. That is particularly true of his work on unity and on the semantic apparatus of self-awareness.